Deciphering the evolution of the functional genes and microbial community of the combined partial nitritation-anammox process with nitrate build-up and its in situ restoration. Issue 113 (24th November 2016) - Wang, Yuanyue; Wang, Hongyan; Zhang, Junya; Yao, Li; Wei, Yuansong
Abstract : The operation of a combined partial nitritation-anammox (CPNA) process was hampered by the overgrowth of NOB, which was then successfully in situ restored by the combination of hydroxylamine (NH2 OH) dosing and sludge retention time (SRT) control. Abstract : The operation of a combined partial nitritation-anammox (CPNA) process was hampered by the overgrowth of nitrite-oxidizing bacteria (NOB), which was then successfully in situ restored by the combination of hydroxylamine (NH2 OH) dosing and sludge retention time (SRT) control. To elucidate the microbial evolution on gene level and the microbial mechanism responding to the NO3 − build-up and in situ restoration in the CPNA process, the qPCR and high-throughput sequencing were used to investigate the evolution of the N-transformation genes and microbial community in this paper. Results showed that the concentrations of amo A and hao were both decreased as well as the hzo along with the NO3 − build-up, however, the nitrite-oxidation encoding gene nxr A was increased. Pearson correlation analysis demonstrated that the gene nxr A was significantly correlated with the NO3 − . After restoration, the abundances of amo A, hao and hzo were increased to 26.58%, 43.56% and 26.17%, respectively, while the growth of nxr A was effectively limited. The obtained high abundance of nar G gene (37.85%) as well as the significant correlation of hzo – nar G and hzo – nir S illustrated the in situ restoring mechanism, i.e., the intensive denitrification of the accumulated NO3 − to NO followed by the stimulation of the anammox by NO. Additionally, MiSeq sequencing showed a new microbial community was rebuilt after restoration and the Haliscomenobacter and Nitrosomonas were the dominant genera. The abundance of anammox genus Candidatus Kuenenia was also increased to 8.0%. The significant correlation between nir K and Ignavibacterium indicated that the filaments played an important role in the denitrification of the accumulated NO3 − .